Promoting Intergenerational Justice Through Participatory Practices: Climate Workshops as an Arena for Young People’s Political Participation - Ursin, Marit; Lorgen, Linn C.; Alvarado, Isaac Arturo Ortega; Smalsundmo, Ani-Lea; Nordgård, Runar Chang; Bern, Mari Roald; Bjørnevik, Kjersti (Frontiers in Psychology, 2021)
In the fall of 2019, Trøndelag County Council, Norway, organized a Climate Workshop for children and youth. The intention of the workshop was to include children’s and youth’s perspectives as a foundation for a policy document titled “How we do it in Trøndelag. Strategy for transformations to mitigate climate change”. The workshop involved a range of creative and discussion tools for input on sustainable development and climate politics. In this article, we aim to (1) describe and discuss innovative practices that include children and youth in policymaking related to climate action, and (2) discuss the theoretical implications of such policymaking in relation to children’s rights, young citizenship, and intergenerational justice. We employ a generational framework and perceive climate politics as inherently ingrained in intergenerational justice, where no generation has a superior claim to the earth’s resources, yet power is unfairly concentrated and accumulated among adult generations. We draw on contributions by various stakeholders involved: Two young workshop participants, two county council policymakers, and an interdisciplinary team of researchers from Childhood Studies and Design.